Regional Financial Performance and Human Development Index Based on Study In 20 Counties/Cities of Level I Region - Gousario, Freska; Dharmastuti, Christiana Fara (Journal the Winners: Economics, Business, Management, and Information System Journal, 2015)
This research aimed to know the financial performance of local government through regional financial ratio analysis, i.e. regional financial independence ratios, regional financial effectiveness ratios, regional financial efficiency ratios and regional expenditure harmony ratios,as well as analyzing the impact of regional financial performance against the Human Development Index (HDI).This research was conducted in 20 counties/cities in level I region. Analysis techniques used was multiple linear regression analysis with SPSS Statistics 21. The results shows that: (1) Ratio of regional financial independence contributes positive and significant effect to HDI, (2) Ratio of the regional financial effectiveness contributes no significant effect to HDI, (3) Ratio of regional financial efficiency contributes no significant effect to HDI, and (4) Ratio of regional financial harmony expenditure contributes no positive effect to HDI.